Relationship between strength development and porosity of epoxy-based mortar - Nur Farhayu, Ariffin; Sharifah Maszura, Syed Mohsin; Khairunisa, Muthusamy; Fadzil, Mat Yahaya; Saffuan, Wan Ahmad (Springer, 2024)
Epoxy resin is conventionally combined with a hardener for the purpose of curing. However, prior research has indicated the potential for epoxy resin to undergo curing in the presence of calcium hydroxide originating from cement hydration. This current study delves into the utilization of commercially accessible epoxy resin without a hardener as an additive in mortars, aiming to enhance mortar strength. The mortar formulations were created with a cement to fine aggregate mass ratio of 1:3, a water-cement ratio of 0.48, and varying epoxy content at 5, 10, 15, and 20% of the cement weight. Subsequent to formulation, the mortars underwent periods of dry curing as well as 5 days of wet curing followed by additional dry curing, all within a tropical environment. The outcomes of the study revealed that the optimal epoxy content for the wet-dry curing process was 10%. Mortars containing 10% epoxy demonstrated notably heightened compressive and flexural strengths compared to the control mortar that lacked epoxy. Over extended dry curing periods, the strength progression of the epoxy-altered mortars exhibited continuous enhancement. Concurrently, the porosity of mortars incorporating epoxy experienced a reduction as the curing duration increased. These findings indicate the viability of epoxy resin devoid of a hardener as a polymeric admixture to augment both the strength and durability of mortars. The ideal epoxy proportion for effective wet-dry curing was determined to be 10%, while the improvement in mortar strength persisted with extended periods of dry curing. Furthermore, the curing period exerted a decreasing influence on the porosity of mortars modified with epoxy.